2020
DOI: 10.1002/tox.23057
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate attenuates the stemness of colorectal cancer cells via trigerring ferroptosis through sequestering iron in lysosomes

Abstract: Colorectal cancer stem cell (CSC) has been regarded to be the root of colorectal cancer progression. However, there is still no effective therapeutic method targeting colorectal CSC in clinical application. Here, we investigated the effects of dichloroacetate (DCA) on colorectal cancer cell stemness. We showed that DCA could reduce colorectal cancer cell stemness in a dose‐dependent manner, which is evident by the decreased expression of stemness markers, tumor cell sphere‐formation and cell migration ability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Subsequently, targeting iron in lysosomes was confirmed to CSC by different studies, 29‐32 and combined use of chemotherapy and salinomycin can boost the capacity of salinomycin to kill CSC and both CSCs and tumor cells are killed 33,34 . Thus, we wonder whether DCA could target iron homeostasis to kill HCC stem cells, this mechanism has been shown in colorectal cancer cells 24 . What's more, based on the KEGG enrichment analysis, some other cancer‐related pathways are also enriched in HCC cells with DCA treatment, such as PI3K‐Akt signaling pathway, which had been shown to be involved in limonin‐mediated inhibition on 35 ; and FOXO signaling pathway, p53 signaling pathway, TNF signaling pathway PPAR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, targeting iron in lysosomes was confirmed to CSC by different studies, 29‐32 and combined use of chemotherapy and salinomycin can boost the capacity of salinomycin to kill CSC and both CSCs and tumor cells are killed 33,34 . Thus, we wonder whether DCA could target iron homeostasis to kill HCC stem cells, this mechanism has been shown in colorectal cancer cells 24 . What's more, based on the KEGG enrichment analysis, some other cancer‐related pathways are also enriched in HCC cells with DCA treatment, such as PI3K‐Akt signaling pathway, which had been shown to be involved in limonin‐mediated inhibition on 35 ; and FOXO signaling pathway, p53 signaling pathway, TNF signaling pathway PPAR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In consistent, DCA‐mediated effects on the stemness of cancer cells were first revealed in pancreatic cancer cells 16 . Notably, a recent study indicates that DCA can also attenuate the stemness of colorectal cancer cells 24 . However, its roles in HCC progression are never been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting iron metabolism using the iron nanoparticles can be used to treat cancer through ferroptosis, which has been approved by FDA [32] . Besides, inducing ferroptosis through sequenstering iron in lysosome has been con rmed to speci cally killing CSCs including BCSCs [10,20,22,23] . In this work, we found CPUL119, CPUL129 and CPUL149 could increase the content of iron in breast cancer cells accompanying with the change of iron-regulatory protein such as IRP2, TfR1 and ferritin.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, it has been shown that salinomycin and its drivatives could target BCSCs through sequestering iron in lysosomes [19][20][21] . Notably, targeting iron in lysosomes has been con rmed to killing CSCs in other tumors, such as nasopharyngeal carcinoma [22] and colorectal cancer [23] . These results amplify that sequestering iron in lysosomes is a promosing method in targeting BCSCs.…”
mentioning
confidence: 99%
“…Scholars have suggested that ferroptosis may be adaptive strategy used for eliminating cancerous cells and hence prevent cancer development in situations of infections, cellular stress, and nutrient de ciency [6]. Previous research has reported that some inducers, such as RSL3 [7], β-elemene [8], Resibufogenin [9], andrographis [10], bromelain [11], IMCA [12], talaroconvolutin A (TalaA) [13], ACADSB [14], erastin [15], dichloroacetate [16], and B. etnensis Raf. extract [17] suppressed the progression of CRC via inducing ferroptosis.…”
Section: Introductionmentioning
confidence: 99%